The Emergence and Evolution of Maqasid al-Shariah in Islamic Fintech Discourse: A Bibliometric and Science Mapping Analysis - Mesi Herawati (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2026)
Purpose – This study maps the scientific development, social and intellectual structure, conceptual structure, and thematic evolution of Maqasid al-Shariah in the Islamic FinTech literature using bibliometric and science mapping approaches. Design/Methods/Approach – Scopus-indexed publications published between 2020 and June 2026 were analyzed using bibliometric techniques, VOSviewer, and the PRISMA 2020 framework. A total of 76 publications were included in the final dataset. Findings – The results indicate increasing scholarly attention to Maqasid al-Shariah in the Islamic FinTech literature, although publication output fluctuated across individual years. Indonesia and Malaysia emerge as leading contributors, supported by prominent authors, institutions, and publication sources. The literature is organized around interconnected themes, including Islamic FinTech, financial inclusion, blockchain, Islamic social finance, sustainability, artificial intelligence, and Shariah governance. Although Maqasid al-Shariah is not among the most frequent keywords, its discourse is connected to these themes, particularly ethical innovation, social welfare, financial inclusion, and sustainability. Thematic evolution suggests a shift in emphasis from technology-oriented innovation toward value-driven and sustainability-focused research. Research Implications/Limitations – This study is limited to Scopus-indexed publications identified through the specified search strategy and covers publications available up to June 2026; therefore, the 2026 publication count represents a partial year. The findings are also sensitive to database coverage, search-term selection, bibliometric thresholds, and citation-time effects. Nevertheless, the study provides a knowledge base for future research on AI, blockchain governance, digital Islamic social finance, ESG, digital Shariah governance, and Maqasid-based performance measurement. Originality/Value – This study demonstrates how Maqasid al-Shariah is increasingly connected with the ethical, social, governance, and sustainability dimensions of Islamic FinTech research and provides a comprehensive knowledge map to inform future research and policy discussions.